THE EFFECT OF PROFITABILITY ON COMPANY VALUE IN PLANTATION COMPANIES LISTED ON THE IDX IN THE 2022-2024 PERIOD - Nurul Nazifah; Revi Candra (Jurnal Akuntansi Syariah (JAkSya), 2026)
Firm value is an important indicator that reflects market conditions regarding a company's performance and opportunities. One internal factor believed to influence firm value is profitability, but empirical research results show mixed findings. The purpose of this study is to analyze the effect of profitability on firm value in the plantation sector listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 period. This study uses a quantitative method with a causality approach. Ten plantation companies were sampled in this study, selected using a purposive sampling technique. Panel data regression was used in data analysis, and the Random Effect Model (REM) was the best model for data analysis. This study found that profitability, as proxied by Return on Assets (ROA), has a significant positive effect on firm value, as proxied by Price to Book Value (PBV). This finding aligns with signaling theory, which states that profitability is a positive signal for investors in assessing a company's prospects.